2000
DOI: 10.1117/12.382907
|View full text |Cite
|
Sign up to set email alerts
|

<title>Classification of optical galaxies using a PCNN</title>

Abstract: Hubbies pioneering discovery of the distance to the Andromeda galaxy opened the frontiers of extragalactic research.According to estimates computed from the Hubble Deep Field, astronomers predict that the universe may potentially contain over 50 billion galaxies. RecognitionlClassification of galaxies is an important issue in the large-scale study of the Universe and is not a simple task. Several techniques have been reported for the classification of galaxies. Artificial neural networks are being successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Several authors have reported work along this line [see Refs. 28-37 in [99]]. The techniques studied include the use of statistical model fitting, fuzzy algebra, decision tree, PCA, and wavelet-based image analysis.…”
Section: Identification and Classification Of Galaxiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported work along this line [see Refs. 28-37 in [99]]. The techniques studied include the use of statistical model fitting, fuzzy algebra, decision tree, PCA, and wavelet-based image analysis.…”
Section: Identification and Classification Of Galaxiesmentioning
confidence: 99%
“…Some work has been reported on the use of artificial neural networks for automatic morphological classification of galaxies; using feed-forward neural network, self-organizing maps, computer vision technique -see Refs. 32-34 in [99]. These techniques, however, require extensive training, hence are computationally demanding and may not be appropriate for the classification of a large number of galaxies.…”
Section: Identification and Classification Of Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation